Projetos de educação e divulgação científica no Brasil: Edgard Roquette-Pinto e a Revista Nacional de Educação (1932-1934) - Wanick, Mariana Calazans (2018)
Understanding the debates and proposals about education and the dissemination of science in the National Journal of Education, a periodical of the National Museum that circulated between the years of 1932 and 1934, is the central objective of this dissertation. In order to better understand the particularities of the publication and its objectives, we carried out the movement of locating it in the context of the discussions about proposals for the development of the Brazilian nation and its viability, a very recurrent debate in the first decades of the twentieth century. Together with this effort to contextualize the journal in the debates of the period in which it was published, we also highlight the search for an understanding of the central aspects of Edgard Roquette-Pinto's thinking and actions. Knowing the work of the doctor, anthropologist and director of the National Museum, Edgard Roquette-Pinto, is a basic element for our work because he was the idealizer and editor of the publication and also director of the museum during the period in which the Journal circulated. Therefore, with this work we propose a reading of the National Journal of Education and we underline its contribution to the debate on education and popularization of science in Brazil at the beginning of the 20th century, in connection with elements of Edgard Roquette-Pinto's trajectory, his actions in favor of education and science, his role as director of the National Museum, as well as his anthropological thought, which was fundamental for his role as educator and vulgarizer of science. Throughout the researches, readings of the periodical and the bibliography, we note a relation of proximity between the publication and the new government that took possession of the Revolution of 1930. From indications such as the own financing of the periodical and the presence of some connected intellectuals to the museum in government decisions, we conclude that the purpose of the journal coincided and married very well, even temporarily, with the government of Getúlio Vargas. We note that publication was only possible thanks to this partnership, even if it was not permanent or guaranteed, it was fundamental for the publication and circulation of this periodical with public funds. It was precisely a change in the balance of power within the Getúlio Vargas government that compromised the continuity of the Revista, which came to an end in 1934. We conclude that the National Journal of Education represented a project of education and scientific dissemination, connected with the anthropology of Edgard Roquette-Pinto's denial of miscegenation as an unfeasible factor in the development of the Brazilian nation, which was accepted and supported by the new federal government represented by Getúlio Vargas's entry into power with the 1930 Revolution.